Journey Towards Self Identity In the Novels of Shashi Deshpande: Exploring the Role of Feminism in Shashi Deshpande's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Feminism and its crusade against a male dominated societyis of special importance in the Indian context. The Indian woman has for yearsbeen a silent sufferer. While she has played different roles- as a wife,mother, sister and daughter, she has never been able to claim her ownindividuality. The words which are always associated with the concept of anideal woman are self-denial, sacrifice, patience, devotion and silentsuffering. But with the rise of feminism, woman became aware of the fact thather inferiority is not ordained in heaven, that gender is neither natural norimmutable, because it is a creation of patriarchy and patriarchy is not given.It is a construct which can be deconstructed. Shashi Deshpande attacks patriarchy, enables matriarchyto emerge as a powerful structure encompassing that ever-widening chasm in amale-female relationship. She criticizes both male and female chauvinism anddislikes Western feminist formulations to avoid proper tenor of femininediscourse in India. She advocates certainly a healthy and mature version offeminism which demands not emancipation for woman but a far better role forher, complementing each other by means of healthy adjustments and truehappiness.